Antioxidants: Are we abusing it? - T G Shrihari; Vijeev Vasudevan; S Kailasam; Devaraju Devaiah; V Manjunath; G R Jagadish (Wolters Kluwer Medknow Publications, 2012)
Oral cancer holds the eighth position in the cancer incidence ranking worldwide. with squamous cell carcinoma encompassing at least 90% of all oral malignancies. The World Health Organization expects that prognosis for many of these patients is grave and even in cases of successful treatment the degree of dysfunction and disfigurement postoperatively is well appreciated by all of us. Hence, understanding of the disease process is of paramount importance for early diagnosis and successful management. Dietary substitutes, such as betacarotene, provitamin A, vitamin A, C, and E, lipoic acid, zinc, selenium and Spirulina use in premalignant lesions, in premalignant conditions is still a debate. The antitumor activity of micronutrients is by their capability of destroying cancer cells through three major mechanisms: (i) Tumor inhibition by immune cytokines; (ii) stimulation of cancer suppressor genes, such as 'wild-type p54' and diminished expression or dysregulation of oncogenes, such as mutant p53 and H-ras; (iii) inhibition of angiogenesis-stimulating factors, such as transforming growth factor alpha (TGFa). Studies have shown that antioxidants are not the' magic bullet' for the treatment of premalignant oral mucosal lesions or the prevention of second primary malignancies. However, there is a role for antioxidants if used judiciously in selected cases that can be monitored carefully. An important principle is that the treatment should not be more harmful than the damage that the lesion can cause.